2019
DOI: 10.1093/ecco-jcc/jjz018
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Therapeutic Drug Monitoring of Adalimumab Is Associated With Better Long-term Outcomes Compared With Standard of Care in Patients With Inflammatory Bowel Disease

Abstract: Background and Aims Therapeutic drug monitoring [TDM] has proven to be effective for optimising anti-tumour necrosis factor [TNF] therapy in inflammatory bowel disease [IBD]. Nevertheless, the majority of data refer to infliximab and reactive testing or association studies. We aimed to compare the long-term outcome of patients with IBD who received at least one proactive TDM of adalimumab, with standard of care, defined as empirical dose escalation and/or reactive TDM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 30 publications
2
82
0
1
Order By: Relevance
“…97 Although well-designed large prospective studies are lacking, there are preliminary data mainly from retrospective studies that demonstrate that proactive TDM is associated with better therapeutic outcomes compared with empiric dose optimization and/or reactive TDM. 38,39,103,104,128 Furthermore, numerous retrospective studies 23,24,26,29,[31][32][33]67,73,74,[77][78][79]129,130 and some post hoc analyses of RCTs [47][48][49]71,76,94,131,132 have shown that higher biologic drug concentrations are associated with favorable short-term and long-term therapeutic outcomes in IBD (Supplementary Table 1, Tables 1 and 2). There do appear to be certain clinical scenarios that proactive TDM of anti-TNF therapy can efficiently guide therapeutic decisions, such as treatment de-escalation, 133 the application of optimized monotherapy instead of combo therapy with immunomodulator, 82 restarting therapy after a long drug holiday, 27 and treatment cessation on deep remission.…”
Section: Discussionmentioning
confidence: 99%
“…97 Although well-designed large prospective studies are lacking, there are preliminary data mainly from retrospective studies that demonstrate that proactive TDM is associated with better therapeutic outcomes compared with empiric dose optimization and/or reactive TDM. 38,39,103,104,128 Furthermore, numerous retrospective studies 23,24,26,29,[31][32][33]67,73,74,[77][78][79]129,130 and some post hoc analyses of RCTs [47][48][49]71,76,94,131,132 have shown that higher biologic drug concentrations are associated with favorable short-term and long-term therapeutic outcomes in IBD (Supplementary Table 1, Tables 1 and 2). There do appear to be certain clinical scenarios that proactive TDM of anti-TNF therapy can efficiently guide therapeutic decisions, such as treatment de-escalation, 133 the application of optimized monotherapy instead of combo therapy with immunomodulator, 82 restarting therapy after a long drug holiday, 27 and treatment cessation on deep remission.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, upper limits have been estimated from clinical observation of the relationship of incremental efficacy with incremental dosing. Papamichael et al divided 382 patients (311 with CD) into quartiles according to the adalimumab levels (Q1: <5.6 µg/mL; Q2: 5.6‐12 µg/mL; Q3: 12‐17.8 µg/mL; Q4: >17.8 µg/mL). Using a proactive TDM strategy, the authors observed higher rates of treatment failure in quartiles 1‐2 (between 56% and 58%) compared to quartiles 3‐4 (between 19% and 23%), suggesting that no additional efficacy was achieved above 17.8 µg/mL.…”
Section: Determination Of the Therapeutic Range For Anti‐tnf Agentsmentioning
confidence: 99%
“…Cost savings may also enable earlier access to biologics in some countries [145,146]. If cost savings were directed toward additional services, therapeutic drug monitoring (TDM) could help optimize TNF inhibitor therapy and deliver personalized care for patients with IBD [147,148]. TDM involves measurement of drug and ADA levels: ADA formation is frequently associated with reduced primary efficacy and loss of response to IBD treatment [50] and may be predicted by factors including drug clearance and body weight [149].…”
Section: Pharmacoeconomists' Perspective: Cost Of and Access To Biolomentioning
confidence: 99%